USER EVALUATION ON ONLINE TRANSPORTATION SERVICE APP FOR UUM STUDENTS: SenangCar - Loh Qiao Way; Yap Houng Ying; Yap Houng Minn; Thu Yue Hen; Azliza Othman; Sobihatun Nur Abdul Salam, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Nowadays, transportation is a major need for people in managing their daily activities such as going to work, school and vacation. Current technology has brought changes in transportation service in many countries. Online transportation services through web and mobile applications are able to attract people’s interest. They can rent or grab a car easily with their fingertips anywhere. However, in Universiti Utara Malaysia (UUM), students faced problems booking and using the existing service. Because UUM is located quite far from the centre and this can cause high cost. Realising this problem, SenangCar, a transportation service application was developed for bringing convenience to the UUM students to book a car service in the UUM area. Agile methodology was adopted to develop the application. This methodology consists of six phases which are requirements, designing, developing, testing, deployment and review. This paper discusses feedback from user evaluation on SenangCar app among UUM students. The findings reveal that this application was easy to understand, easy to use and very satisfied the students. Majority of participants strongly agree that the SenangCar application is convenient, saves time, is user friendly and meets their expectations and requirements.